Discovery of a Roman Quarry for Pozzolanic aggregates in the Euganean Hills Magmatic District, Northeast Italy: A stepwise archaeometric approach - Simone Dilaria; Luigi Germinario; Claudio Mazzoli; Caterina Previato; Milo K. Pilgrim; Josiah Olah; Jacopo Nava; Jacopo Bonetto; Michele Secco (PLoS ONE, 2026)
This study investigates the provenance of volcanic aggregates used in Roman lime-based mortars from the theatre–bath complex at Via Scavi in Montegrotto Terme (ancient Fons Aponi , northeastern Italy), dated to the Early Imperial period. An integrated stepwise archaeometric approach combining petrographic observations via Transmitted Polarized Light-Optical Microscopy (TPL-OM), mineralogical analyses via Quantitative Phase Analysis-X-Ray Powder Diffraction (QPA-XRPD), bulk geochemical data via X-Ray Fluorescence (XRF), microchemical analyses via Scanning Electron Microscopy coupled with Energy-Dispersive Spectroscopy (SEM-EDS), and µ-Raman Spectroscopy were applied to characterize the volcanic components of the mortars and assess their hydraulic behaviour. The results show that the mortars incorporate angular trachytic to trachyandesitic volcanic breccias displaying well-developed reaction rims and extensive pozzolanic reactivity, leading to the formation of calcium–aluminosilicate hydrate phases typical of pozzolanic lime mortars. Comparison with a comprehensive reference database of volcanic rocks from the Euganean Hills Magmatic District (Veneto, Italy) indicates that these aggregates are consistent with explosive diatreme breccias exposed in the eastern sector of the district, most likely corresponding to quarry sites near Villa Draghi (Montegrotto Terme). The identification of these volcanic materials in mortars from Aquileia (northeastern Italy, approximately 150 km north-east of the Euganean Hills) further suggests that such “Euganean pozzolans” were not used exclusively at a local scale but were traded over longer distances. These findings provide new archaeometric evidence for the exploitation of non-Vitruvian volcanic pozzolans in Roman construction and illustrate the potential of integrated petrographic and geochemical approaches for provenance studies of these mortar aggregates.